Pengembangan Perangkat Pembelajaran Materi Perbandingan Berbasis Pendekatan Matematika Realistik - Mega Husriani Kunta; Victor R. Sulangi; Rosiah J. Pulukadang (Journal on Education, 2023)
This research is a development research which aims to produce learning tools on the subject of Cubes and Blocks in class VII SMP with a realistic mathematics approach. The procedure used in this study refers to the Thiagarajan learning device development model (4-D Model) which is modified to 3-D. This research was conducted with limited trials so it needs to be developed to measure validity, effectiveness and practicality. The results of this research show that the learning tools include LKPD, THB and RPP according to valid criteria, so they can be used in learning outcomes tests, namely; 40.7% with a standard deviation of 11.64% from the ideal score of 100, with 32 students, student and teacher activities tend to be positive, student responses to learning tools tend to be positive, active and creative. From the results of the research above, it can be concluded that by using Comparative Learning Materials Based on a Realistic Mathematics Approach for class VII students at SMP Negeri 3 Tondano, students' readiness and understanding in the learning process can develop well.